MELIHAT HIPERREALITAS GENERASI Z DAN PERAN PENTING AGAMA SEBAGAI KONTROL SOSIAL - Permadi, Danur Putut; Yantari, Hanif Fitri (UIN Raden Mas Said Surakarta, 2023)
This research aims to trace the forms of hyperreality that occur in generation Z and analyze the position of religion in addressing generation Z's problems. This research is motivated by the social changes of the generation Z. As a generation born and grows in the digital age, often generation Z chooses